Neurochemical and electrical modulation of the locus coeruleus: contribution to CO2drive to breathe - de Carvalho, Débora; Patrone, Luis G. A.; Taxini, Camila L.; Biancardi, Vivian; Vicente, Mariane C.; Gargaglioni, Luciane H. (Frontiers in Physiology, 2014)
The Locus coeruleus (LC) is a dorsal pontine region, situated bilaterally on the floor of the fourth ventricle. It is considered to be the major source of noradrenergic innervation in the brain. These neurons are highly sensitive to CO2 / pH, and chemical lesions of LC neurons largely attenuate the hypercapnic ventilatory response in unanesthetized adult rats. Developmental dysfunctions in these neurons are linked to pathological conditions such as Rett and sudden infant death syndromes, which can impair the control of the cardio-respiratory system. LC is densely innervated by fibers that contain glutamate, serotonin and ATP, and these neurotransmitters strongly affect LC activity, including central chemoreflexes. Aside from neurochemical modulation, LC neurons are also strongly electrically coupled, specifically through gap junctions, which play a role in the CO2 ventilatory response. This article reviews the available data on the role of chemical and electrical neuromodulation of the LC in the control of ventilation.